Efeito de culturas de cobertura e manejo da palhada sobre os componentes de produção de crambe - Bassegio, Doglas [UNESP]; Santos, Reginaldo Ferreira; Secco, Deonir; Werncke, Ivan; Sarto, Marcos Vinícius Mansano [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2015)
The objective of this study was to evaluate the dry matter (DM) yield and nutrient accumulation in cover crops and the effect of these, as well as mechanical management of crop residues on growth and grain yield of crambe (Crambe abyssinica). The experiment was conducted in Santa Helena, Paraná, Brazil in Rhodic Hapludox (Red Latosol in the Brazilian classification) in experimental design of randomized complete blocks with four replications in a split-plot. The plots were: Pearl millet (Pennisetum glaucum), grass brachiaria (Brachiaria brizantha), forage sorghum (Sorghum bicolor) and sunn hemp (Crotalaria juncea) and an area fallow (spontaneous weed) and the sub-plots, the mechanical or not management of crop residues on the soil surface (Triton©). Grass brachiaria produced less amount of DM and showed less accumulation of nutrients. Other cover crops did not differ in DM production, but the sunn hemp showed the highest concentrations of N and Ca, while pearl millet P. The mechanical management of crop residues on the soil surface not influence the yield components of crambe, however provides higher final plant density. The crambe grown after sunn hemp showed higher DM accumulation (1,826 kg ha–1) and grain yield (1,066 kg ha–1).
Effect of cover crops and straw management on yield components of crambe
Keywords: Cover crops; Crambe abyssinica; Nutrient cycling; Straw management